Administration of intravenous benzylpenicillin in 13 infants born to mothers with syphilis infection: A case series. Issue 11 (November 2021) - Ikuta, Toshihiko; Abe, Shinya; Suga, Shutaro; Nakasone, Ruka; Ashina, Mariko; Tanimura, Kenji; Nozu, Kandai; Fujioka, Kazumichi
Abstract: The incidence of syphilis infection among pregnant women is persistently high in Japan and in several developed countries. Here, we report the utility of intravenous benzylpenicillin in 13 infants born to mothers with syphilis infection. Because the recommended treatment (intramuscular benzathine benzylpenicillin) is not available in Japan, we intravenously administered benzylpenicillin for 10 days, which is used for treatment in high-risk cases. The administration of benzylpenicillin in low-risk infants resulted in an extended duration of parent-to-infant separation and increased the infants' exposure to invasive procedures. Thus, establishing evidence of the adequacy of no-treatment follow-up in low-risk groups and introducing intramuscular injections of benzathine benzylpenicillin may improve the management of infants suspected with congenital syphilis in Japan.